Exploring High School Students' Understanding of Critical Pedagogy in Interpreting English-Language Digital Content on Social Media - Noni Trisna Putri; Slamet Wahyudi Yulianto; Muhammad Anjar Nugraha (Universitas Subang, 2026)
This research examines how Indonesian senior high school students engage with English language material on social media, drawing on critical pedagogy principles. Through in-depth interviews with two students, the conversations were analyzed to explore their interpretation of digital texts, encompassing underlying power dynamics and ideologies. Key results indicate that social media serves as an enjoyable platform for English learning, such as via videos and posts, yet linguistic challenges frequently impede thorough comprehension and critical analysis. Factors like apprehension about errors, anxiety, and imbalanced classroom dialogues result in students remaining passive and engaging only superficially with topics. Nonetheless, they are beginning to recognize diverse viewpoints on societal issues, although translating these insights into action proves difficult. The study concludes that fostering critical thinking in English education requires a comprehensive strategy, incorporating language assistance, supportive atmospheres, and inclusive discussions to empower student development. Further research should involve extended periods and wider contexts to advance digital content literacy.